HUBUNGAN ANTARA PERENCANAAN KEPALA RUANG DENGAN PENANGANAN PASIEN HIV/AIDS - Yulia Ardiyanti; Eka Listiana; Teguh Anindito; Siti Aminah (Jurnal Surya Muda, 2021)
The function of nursing management, especially the planning function of the head of the room, is important to realize quality nursing services, especially in the treatment of patients with HIV/AIDS. The purpose of this study was to determine the relationship between the planning function of the head of the room with the treatment of HIV/AIDS patients in dr. H. Soewondo Kendal. This study with a sample of 58 people used a descriptive correlation design with a cross sectional approach, using bivariate analysis with the Spearman Rank test. The results of the bivariate analysis showed that there was a significant relationship between the planning function and the treatment of HIV/AIDS patients in RSUD dr. H. Soewondo Kendal (pvalue 0.001). Recommendations for the hospital nursing management to improve the planning function in terms of providing supporting facilities for handling HIV/AIDS such as SAK HIV/AIDS, syringe supplies and syringe disposal sites and universal precaution training.